High storage capacity and small volume change of potassium-intercalation into novel vanadium oxychalcogenide monolayers V2S2O, V2Se2O and V2Te2O: An ab initio DFT investigation - Yu, Yang-Xin (Applied surface science, 2021)
[Display omitted] •V2Ch2O monolayers exhibit highly mechanic, dynamic and thermal stabilities.•V2Ch2O monolayers have high storage capacities of potassium.•Lattice parameter changes are within 7.26% duaring K-intercalation.•There is no phase transition during K-intercalation, avoiding potential hysteresis.•V2S2O monolayer is a promising electrode material for K-ion batteries. A new category of two-dimensional electrode materials, i.e., V2Ch2O (Ch = S, Se and Te) monolayers was explored for K-ion batteries (PIBs) based on principle of chemical exfoliation, density functional theory and ab initio molecular dynamics simulations. The V2Ch2O monolayers show low cleavage energies and excellent thermal, dynamical and mechanical stabilities. Adsorption energies of a potassium atom on the V2Ch2O monolayers are exothermic, which are of benefit to prevent forming dendrites. The existence of electrode potentials substantially decreases the diffusion barriers of potassium atoms on the three V2Ch2O monolayers. The V2Ch2O monolayers are able to maintain their metallic characteristics and single surface phase during the whole K-intercalation process, avoiding the decrease in electronic conductivity and the appearance of potential hysteresis. The theoretical specific capacities of the V2S2O, V2Se2O and V2Te2O monolayers are predicted to be 883.6, 583.1 and 431.0 mAh g−1, respectively, and the corresponding average open-circuit voltages are 0.449, 0.390 and 0.293 V, respectively. The maximum percentage changes in lattice parameters are 4.21%, 6.07% and 7.26% for the V2S2O, V2Se2O and V2Te2O monolayers, respectively. All the calculated properties indicate that the V2Ch2O monolayers are promising electrode materials for PIBs with high capacities and long cycle lives.